Assessing the Impact of "The Collapse" on the Organization and Content of Autobiographical Memory in the Former Soviet Union. (June 2015) - Nourkova, Veronika V.; Brown, Norman R.; Hunter, Andrea G.; Stewart, Abigail J.
<x xml:space="preserve">Abstract</x> It can be argued that the Collapse of the Soviet Union was the most important historical event of the past 50 years. This study assessed the mnemonic impact of this event in Russia, Azerbaijan, and Uzbekistan. It involved three tasks. First, participants thought aloud as dated autobiographical events. Second, they drew a personal timeline. Finally, they answered questions concerning the psychological and material consequences of the Collapse. Across the samples, we found (1) the Collapse was almost never used as a temporal landmark, (2) it was rarely included in timeline drawings, and (c) participants did not experience the Collapse as a major life‐changing event. These findings argue against the Proportionality Assumption—the notion that the mnemonic impact of a public event is related to its historical importance. Instead, they suggest that historically significant events play an important role in autobiographical memory only when they dramatically affect people's material circumstances.